1982
DOI: 10.1289/ehp.8244175
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of polybrominated biphenyls (PBBs) in Domestic and laboratory animals.

Abstract: The composition, environmental fate, and effects of the polybrominated biphenyls (Firemaster BP-6 or FF-1) involved in the accidental contamination of cattle feed in Michigan in 1973 are reviewed. Toxic effects referred to in this report are limited to those occurring in domestic and laboratory animals and include general toxicity, neurobehavioral toxicity, immunotoxicity, reproductive toxicity, mutagenicity and carcinogenicity. The absorption, distribution, biotransformation and elimination of these polybromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 103 publications
0
4
0
3
Order By: Relevance
“…25,31 A absorção dos PBBs pelos organismos ocorre de forma rápida e inversamente proporcional ao número de bromos na molécula. 44 Devido a sua característica de lipofilicidade, as maiores concentrações são encontradas, principalmente, nos tecidos hepático e adiposo. 44 Além disso, estudos feitos com humanos mostraram que a transferência placentária ocorre, porém a principal forma de excreção em mamíferos é através do leite.…”
Section: Bifenilas Polibromadas (Pbbs)unclassified
See 2 more Smart Citations
“…25,31 A absorção dos PBBs pelos organismos ocorre de forma rápida e inversamente proporcional ao número de bromos na molécula. 44 Devido a sua característica de lipofilicidade, as maiores concentrações são encontradas, principalmente, nos tecidos hepático e adiposo. 44 Além disso, estudos feitos com humanos mostraram que a transferência placentária ocorre, porém a principal forma de excreção em mamíferos é através do leite.…”
Section: Bifenilas Polibromadas (Pbbs)unclassified
“…44 Devido a sua característica de lipofilicidade, as maiores concentrações são encontradas, principalmente, nos tecidos hepático e adiposo. 44 Além disso, estudos feitos com humanos mostraram que a transferência placentária ocorre, porém a principal forma de excreção em mamíferos é através do leite. 46,47 A meia-vida desses compostos nos organismos é bastante variável, por exemplo, 22 dias em porquinhos--da-índia a 4 anos em macacos.…”
Section: Bifenilas Polibromadas (Pbbs)unclassified
See 1 more Smart Citation
“…(Eyster et al, 1983;Miceli et al, 1985). Animal studies have suggested thyroid, hepatic, reproductive, cancer, and developmental effects after high levels of oral exposure to PBB (Damstra et al, 1982;ATSDR, 2004). In exposed individuals, PBBs are partially metabolized and excreted in feces or stored in fatty tissues where they persist for many years (ATSDR, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14 It is possible that exposure to PBB or PCB might modify the local response to HPV infection. Furthermore, PBB exposure has been shown to cause immunosuppression in laboratory animals 15 ; immunosuppression resulting from such conditions as systemic lupus erythematosus 16 and AIDS 17 is associated with an increased risk of cervical dysplasia and cancer. Because of their role as potential endocrine disruptors, PBBs or PCBs might induce dysplastic changes in squamous or glandular cells of the ectocervix or endocervix and might affect the transformation zone where cells are sampled for Pap tests and where cervical cancers arise.…”
mentioning
confidence: 99%